Problematika Guru PAI Realita Dan Idealita Sebagai Akuntabilitas Sosial - Hasyim, Sukarno L. (STAI Miftahul Ula Nganjuk, 2015)
Abstract: Problematic Islamic Education Teachers (PAI) is a gap / difference between desired in the implementation of the learning process carried out by the Islamic Education Teachers, so the results are not in accordance with the desired objectives and the problem either comes from the teacher and of the learning process of school. While the reality and idealist as social accountability is a fact and a desire to be possessed by an ideal teacher. The ideal teacher according to the guidance of Islamic law is behaving imitate the Prophet Muhammad. Meanwhile, according to the legal provisions of the country is having the competence standards as mandated by the PP. No. 19 of 2005 on National Education Standards. In addition, as the responsibility of a teacher as a public official, the teacher is the servant of the state and public servant.